PENGARUH BOTTOM ASH SEBAGAI PENGGANTI PASIR DAN LIMBAH KARBIT SEBAGAI BAHAN TAMBAH SEMEN TERHADAP BERAT JENIS, KUAT TEKAN, DAN ABSORBSI BATAKO - Nur Ali; Rofikatul Karimah; H. E.Meiyanto (Media Teknik Sipil, 2014)
PENGARUH BOTTOM ASH SEBAGAI PENGGANTI PASIR DANLIMBAH KARBIT SEBAGAI BAHAN TAMBAH SEMENTERHADAP BERAT JENIS, KUAT TEKAN, DAN ABSORBSIBATAKONur Ali1, Rofikatul Karimah2 , H. E.Meiyanto31,2,3 Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144Email: rofikatulkarimah@gmail.comABSTRACTBasically concrete brick is formed from cement, sand and water, than a breakthroughmade in manufacturing of concrete brick with the utilization of wastes which have no economicvalue are also widely available in the environment than is waste of bottom ash an carbide. In thisresearch, a normal concrete brick consist of cement, san, and water which given variation ofcarbide waste ranging from 10%, 20%, and 30%, afterwards a replacement of sand by bottomash is made with a given variation of carbide waste 10%, 20%, and 30%. Result of the researchthat applying sand as subtle aggregate and waste of carbide as additional material for cementgets the best result on the variation of carbide waste 30% with strength of compression 69,10MPa and 3,58% absorption capacity, it is better rather than normal concrete brick on the variationof carbide waste 0% with compressive strength of 48,74 MPa and 5,49 absorption capacity.After wards, by doing replacement of sand with bottom ash as subtle aggregate and addedwaste carbideas its variations is obtained the best results in the variation of carbide waste 30%with compressive strength 52,37 MPa and 6,92 of absorption capacity better rather than 0% ofvariation carbide waste with strength of compession 19,64 MPa and 12,01 of absorption capacity.Keyword: Concrete Brick, bottom ash, waste carbide.